Implementation of Health Information Systems in Health Care Facilities in North Sumatra: A Literature Review - Diwanta, Faradilla; Maghfirah, Suci; Febrina, Dea; Marwa Simatupang, Nabilah Aprilia; Gunawan, Muhammad Khair; Purba, Sri Hajijah (Universitas Ibn Khaldun Bogor, 2025)
This research contains information on how to implement a health information system in health service facilities in North Sumatra. This research uses a library search or literature study. To search for data on literacy studies, you can refer to books, research journals published locally and internationally, scientific writings, research conducted by others. The results of the research showed that out of 10 journals related to the implementation of health information systems in health services, it can be concluded that health information systems are very important in improving the efficiency, effectiveness and quality of health services. Health information systems (HIS) play a role in managing important data and information in an accurate and timely manner to support the development of public health.